2019
DOI: 10.1186/s12891-019-2550-z
|View full text |Cite
|
Sign up to set email alerts
|

Joint hypermobility is not positively associated with prevalent multiple joint osteoarthritis: a cross-sectional study of older adults

Abstract: Background This cross-sectional study evaluated associations of joint hypermobility and multiple joint osteoarthritis (MJOA) in a community-based cohort of adults 45+ years of age. Methods MJOA and joint hypermobility data were from 1677 participants (mean age 69 years, 68% women) who completed research clinic visits during 2003–2010. Prevalent MJOA was defined in four ways. Radiographic OA (rOA) was defined as Kellgren-Lawrence (KL) > 2 at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
(38 reference statements)
0
11
1
Order By: Relevance
“…Such sparse and unremarkable associations between generalized joint hypermobility and knee health were also noted in other recent studies. 18,29,30 However, our study is in stark contrast to that of a large Danish study. 12 They found that those with knee-specific and generalized joint hypermobility were twice as likely to report symptoms, poorer QoL, and functional limitations.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Such sparse and unremarkable associations between generalized joint hypermobility and knee health were also noted in other recent studies. 18,29,30 However, our study is in stark contrast to that of a large Danish study. 12 They found that those with knee-specific and generalized joint hypermobility were twice as likely to report symptoms, poorer QoL, and functional limitations.…”
Section: Discussioncontrasting
confidence: 82%
“…9 Subsequent studies reported similar findings in Caucasians, [10][11][12] African-Americans, 13 and Middle Eastern populations. 14,15 Conversely, other studies suggest generalized joint hypermobility as a factor protecting hypermobile Caucasians [16][17][18] and African Americans 17,18 from developing osteoarthritis. Such conflicting results regarding the association between generalized joint hypermobility or knee-specific hypermobility with knee health and pain may be explained by the diverse set of outcome measures and their suggested reference values/cut-offs used to quantify these factors.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, hypermobility found to increase the risk of OA [22]. A study investigating the relationship between hypermobility and multiple joint OA did not nd any relationship [23].…”
Section: Discussionmentioning
confidence: 92%
“…Complications can include joint pain, dislocations and instability which can limit daily activities and quality of life. Previous research has highlighted that there may be a link between JH and development of osteoarthritis secondary to the increased stress placed on joints, however studies have reported mixed findings [ 4 , 5 , 6 , 7 , 8 , 9 ]. Although JH has disadvantages linked to increased risk of injury and anxiety, particularly in contact sports, in others such as gymnastics and ballet it may in fact be advantageous [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%